מקור ותרגום בצל העימות: על תרגום האופסימיסט ואח’טיה לעברית - אבו מוך הודא (מכאן, 2017)
This article deals with Emil Habiby’s The Pessoptimist (1974/1984) and Ekhtayyeh(1985/1988), while focusing on source writing and translation. Habiby’s writingexposes his developing inclination of writing with the intention of being translated into Hebrew, which began following the translation of The Pessoptimistinto Hebrew. This article describes a process whereby the writer adopts thetranslator’s political vision, as illustrated in the writing of Ekhtayyeh, which unlike The Pessoptimist was written as a hybrid text that assumed the presence of bothArab and Jewish readers. Habiby’s writing process was influenced by Shammas’ translation project. In his translation of The Pessoptimist Shammas had utilizedstrategies for making Habiby’s works more acceptable to the Hebrew culture, while softening their Arabness so as to serve his political vision of "a state of all its citizens." At the same time, this article points out acts of resistance within the translation. Indeed, Shammas’ cooperation with the hegemonic discourse can be read as a camouflage intended to soften other translation acts that undermine the principles of this discourse, to redesign it in a way that would include the Arab citizens of the state and make the repressed narrative present at the very heart of the ruling culture.